Exploration of the Implementation of BKKBN Policies in Stunting Management: A Fundamental Study on Program Effectiveness and Intervention Strategies - Zahera Mega Utama; Abdul Wahab Samad (PT. Mega Mas Abadi Konsultan, 2025)
Stunting is a complex issue that requires a multidisciplinary approach. Nutritional factors, economic policies, food technology innovations, and optimizing the role of healthcare workers are key elements in its prevention efforts. A multisectoral approach based on scientific evidence is the main strategy in addressing this issue sustainably. This study aims to evaluate the effectiveness of stunting management policies, particularly in the implementation of the PNPK Stunting, Local PMT program, and PKMK. Furthermore, this research seeks to enhance the accuracy of intervention targeting by analyzing the effectiveness of nutrition programs in reducing stunting rates and the factors influencing them. An analysis of socio-economic factors is also conducted to understand the role of maternal education, income levels, and access to healthcare services in influencing stunting prevalence. The results of this study provide policy recommendations that are more targeted, including optimal strategies for implementing community-based nutrition programs tailored to the needs of the population, enhancing the capacity of healthcare workers, and developing more effective community-based intervention models to increase awareness among pregnant and breastfeeding mothers about balanced nutrition